A longitudinal examination of the association between nurse staffing levels, the practice environment and nurse-sensitive patient outcomes in hospitals. Issue 1 (June 2015) - Chau, Janita; Lo, Suzanne; Choi, K.; Chan, Eric; McHugh, Matthew; Tong, Danny; Kwok, Angela; Ip, W.; Lee, Iris; Lee, Diana
Abstract Background The level of patient safety and outcomes accomplished depends on the quality of care provided. Previous studies found that nurse-to-patient ratio, practice environment, and nursing education were significant predictors of patient outcomes. However, the outcomes measured in previous studies were mainly inpatient mortality and failure-to-rescue rates. Few nurse-sensitive patient outcomes have been measured that quantify nurses' contribution to patient care. Selecting appropriate outcomes that reflect the clinically relevant effect of nursing care is important. Moreover previous studies were largely cross-sectional and retrospective. These research designs are limited in their ability to explain the casual links between the variables examined. This study is aimed at determining the associations among staffing levels, skill mix of baccalaureate-prepared registered nurses, and practice environment on nurse-sensitive outcomes for medical and surgical patients in public hospitals in Hong Kong. Method/designs A multi-method research design will be adopted. The sample includes all medical and surgical wards of four major public hospitals that offer 24-h accident and emergency services. Multiple responses from registered nurses who work in the study wards will be collected over 12 months to examine their individual characteristics and perceptions of the practice environment. A 12-month prospective observational study will be performed to determine the association between nurse staffing levels, the practice environment, and nurse-sensitive patient outcomes including pressure ulcers, falls and restraint prevalence, urinary catheter-associated urinary tract infections, and central line catheter-associated bloodstream infections. Multilevel Cox proportional hazards models will be employed to examine the association between these patient outcomes and the explanatory nursing factors of primary interest (nurse staffing levels, education composition, and practice environment), with adjustment for all patient-, ward- and hospital-level potential confounders (age, sex, diagnosis, comorbidities, level of surgical invasiveness, mortality, length of stay, and type of admission). Discussion It is anticipated that knowledge of the association between nurse staffing levels, the practice environment, and nurse-sensitive outcomes will inform the provision of quality and timely patient care. This study will provide a landmark report that is of relevance and importance to patients and to hospital stakeholders and managers, health policy makers, nurses, and educators who advocate patient benefits. Trial registration Clinical Trials RegistryCCTCTR CUHK_CCT00460 . Date of trial registration: 02 July 2015.